Iowa RBA, March 9, 1998 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1998)
Notes for the Iowa RBA for March 9, 1998. Highlights include Tundra Swan, Trumpeter Swan and Greater White-fronted Goose. Includes hand written notes in preparation for next week's update. Epson - sheet feed/flatbed